2018
DOI: 10.1155/2018/4280312
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and Jaw Abnormalities in Panoramic Radiography of Chronic Liver Failure Patients

Abstract: Introduction Patients with chronic liver failure (CLF) are faced with many complications, because this organ is involved in various metabolic activities. Hepatic osteodystrophy is one of the major health issues encountered by this group of patients. The current study evaluated osteoporosis and bone changes in oral panoramic radiographies of cirrhotic patients. Materials and Methods In this study, 138 panoramic views of CLF patients, candidates for liver transplant (65 females, 73 males, aged 19-68 years) refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
(53 reference statements)
0
8
0
7
Order By: Relevance
“…Furthermore, periapical [20,21]. Hence, the existence of oral and dental problems causes pain and discomfort, disturbs the patient's nutrition, and affects appearance and esthetics, all of which can influence their quality of life [3,20]. We found that with an increase in the DMFT index, the quality of life was significantly reduced in CLF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, periapical [20,21]. Hence, the existence of oral and dental problems causes pain and discomfort, disturbs the patient's nutrition, and affects appearance and esthetics, all of which can influence their quality of life [3,20]. We found that with an increase in the DMFT index, the quality of life was significantly reduced in CLF patients.…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown, end-stage liver disease patients are prone to oral infections compared to healthy individuals [3]. Furthermore, periapical [20,21]. Hence, the existence of oral and dental problems causes pain and discomfort, disturbs the patient's nutrition, and affects appearance and esthetics, all of which can influence their quality of life [3,20].…”
Section: Discussionmentioning
confidence: 99%
“…A variação de faixa etária foi menor do que aquele estudo realizado com pacientes à espera de transplante de fígado no Irã (GHAPANCHI et al,2018), e com variação etária maior àquela apresentada no estudo com pacientes com doença renal crônica iranianos (ABDINIAN et al, 2019).…”
Section: Discussionunclassified
“…Inspeções visuais não são suficientes para detectar várias doenças bucais que afetam o tecido subgengival ou são escondidas pelo esmalte dentário (KWEON et al, 2018). Embora um estudo radiográfico de boca toda seja superior a uma radiografia panorâmica, ambos os exames podem ser necessários para maximizar a quantidade de informação radiográfica disponível antes da realização de um transplante de medula ou sobre pacientes que possuem falência crônica hepática que esperam por um transplante, por exemplo (BISHAY et al, 1999;GHAPANCHI et al, 2018).…”
Section: Introductionunclassified
“…Also a reduction in bone mineral density is related to thin mandibular cortical width. (12,13) In a recent study, the correlation between MI, age and BMD at the lumbar spine, femoral neck and total hip were evaluated.…”
Section: Introductionmentioning
confidence: 99%